N-Chlorinative Ring Contraction of 1,4-Dimethoxyphthalazines via a Bicyclization/Ring-Opening Mechanism - Im, Jeong Kyun; Jeong, Ilju; Yang, ByeongDo; Moon, Hyeon; Choi, Jun-Ho; Chung, Won-jin (Synthesis, 2020)
An unprecedented N-chlorinative ring contraction of 1,2-diazines was discovered and investigated with an electrophilic chlorinating reagent, trichloroisocyanuric acid (TCICA). Through optimization and mechanistic analysis, the assisting role of n-Bu4NCl as an exogenous nucleophile was identified, and the optimized reaction conditions were applied to a range of 1,4-dimethoxyphthalazine derivatives. Also, an improvement of overall efficiency was demonstrated by the use of a labile O-silyl group. A bicyclization/ring-opening mechanism, inspired by the Favorskii rearrangement, was proposed and supported by the DFT calculations. Furthermore, the efforts on scope expansion as well as the evaluation of other electrophilic promoters revealed that the newly developed ring contraction reactivity is a unique characteristic of 1,4-dimethoxyphthalazine scaffold and TCICA.
Keywords: halogenation; heterocycles; trichloroisocyanuric acid; ring contraction; phthalazine; phthalimide